Recent Advances in Toxoplasma gondii Infection and Toxoplasmosis - Vinícius Longo Ribeiro Vilela; Thais Ferreira Feitosa (Tropical Medicine and Infectious Disease, 2024)
Toxoplasmosis, caused by the protozoan Toxoplasma gondii, affects nearly all warm-blooded animals, including humans, domestic animals, and both terrestrial and marine wildlife [...]